Analisis Keanekaragaman Plankton Sebagai Indikator Kualitas Perairan Pantai Batu Gosok Kecamatan Komodo Kabupaten Manggarai Barat Nusa Tenggara Timur - Rasjid, Yusniar (bionature, 2017)
Abstract. This research aims to know and analyze the plankton diversity and water quality of Batu Gosok Beach in three research locations: sand location, waste location and mangrove location. Population in this research is all plankton contained in coastal waters of rubbing stone and sample taken by Purposive Sampling method. The results of plankton research in three locations were Diversity (H`) of coastal location: 0.732, waste location: 0.71 and mangrove location 0.777. Index Domination of sand location: 0.24, waste location: 0.22 and mangrove location 0.21, Index Abundance of sand location: 1.99, waste location: 1.18, and mangrove location: 1.72, uniformity index of sand location: 0.66, waste location: 0.71 and mangrove location: 0.75. The quality of the coastal waters of Batu Gosok Beach is still good for the survival of plankton animals.Keywords: diversity, plankton, water